Ultrathin 2D‐Layered Cyclodextrin Membranes for High‐ Performance Organic Solvent Nanofiltration - Huang, Tiefan; Puspasari, Tiara; Nunes, Suzana P.; Peinemann, Klaus‐Viktor (Advanced functional materials, 2020)
Synthetic membranes with a high selectivity for demanding molecular separations and high permeance have a large potential for the reduction of energy consumption in separation processes. Herein, for the first time, the fabrication of an ultrathin layered macrocycle membrane for molecular separation in organic solvent nanofiltration using per‐6‐amino‐β‐cyclodextrin as a monomer for membrane manufacturing by interfacial polymerization is reported. Compared to a regular nonfunctionalized cyclodextrin, a higher reactivity is observed, enabling a very fast membrane formation under mild conditions. The formed membrane is composed of a layered structure of polymerized cyclodextrin, which shows high stability in different organic solvents. The membrane exhibits excellent separation performance for organic solvent nanofiltration, both with nonpolar and polar solvents. Most importantly, this new membrane type can discriminate between molecules with nearly identical molecular weights but different shapes. The unmatched high permeance and shape selectivity of the membranes can be attributed to the ultralow thickness, controlled microporosity, as well as the layered macrocycle structure, which makes the membranes promising for high‐performance molecular separation in the chemical and biochemistry industry. Ultrathin 2D‐layered polymeric macrocycle membranes consisting of amino‐cyclodextrin are prepared via interfacial polymerization in mild condition. The membrane is chemically robust and exhibits excellent separation performance for organic solvent nanofiltration, both with nonpolar and polar solvents. Interestingly, this new membrane type can discriminate between molecules with nearly identical molecular weights but different shapes.